Evaluation of calcium disodium edetate in treatment of lead acetate toxicity (experimental model for human disease) - Imad Ibrahim Ali Al-Sultan; O. E.Ibrahim; T.A. Makkawi (2012)
The study was designed to evaluate the morphological changes of tissue in acute and sub acute toxicity using chicken for experimental induction of toxicity with lead acetate(LA) and treatment by calcium disodium edentate (CDE). Forty five 7 week-old broiler chicken of Ebba2000 breed were used in the experiment. A total of 21 birds were used to estimate the toxic dose was divided into 7 groups. Each group of 3 birds was treated with different doses of LA. The toxic dose was found to be 2 gm/kg bw (Al-Sultan, 2011). The remaining 24 broilers were divided into 3 groups, two of them of 10 birds each. The third group of 4 broilers was not treated and used as a control. To induce acute and sub acute toxicity with the lead compounds, both groups 1 & 2 were given the toxic dose in an amount of 2 gm/kg bw. Both groups were treated with 5% (CDE) immediately after the appearance of the toxicity signs. birds with acute singe of toxicity showed highly significant and reductive response in pathomorphology changes imposed by lead when treated by 5% CDE, while birds suffer of sub acute pathological alterations due to resist the regression of changes after treatment with 5% CDE and tissue damage was persistent and non reversible. However, a negative correlation between the concentration of LA in the blood and the intensity of damage to the tissue was existed.